Elevated Terminal C5b-9 Complement Complex 10 Weeks Post Kidney Transplantation Was Associated With Reduced Long-Term Patient and Kidney Graft Survival - Witczak, Bartlomiej J.; Pischke, Søren E.; Reisæter, Anna V.; Midtvedt, Karsten; Ludviksen, Judith K.; Heldal, Kristian; Jenssen, Trond; Hartmann, Anders; Åsberg, Anders; Mollnes, Tom E. (Frontiers in Immunology, 2021)
Background: The major reason for graft loss is chronic tissue damage, as interstitial fibrosis and tubular atrophy (IF/TA), where complement activation may serve as a mediator. The association of complement activation in a stable phase early after kidney transplantation with long-term outcomes is unexplored. Methods: We examined plasma terminal C5b-9 complement complex (TCC) ten weeks posttransplant in 900 patients receiving a kidney between 2007 and 2012. Clinical outcomes were assessed after a median observation time of 9.3 years (IQR 7.5-10.6). Results: Elevated TCC plasma values (≥0.7 CAU/mL) were present in 138 patients (15.3%) and associated with a lower 10-year patient survival rate (65.7% versus 75.5%, P<0.003). Similarly, 10-year graft survival was lower with elevated TCC; 56.9% versus 67.3% (P<0.002). Graft survival was also lower when censored for death; 81.5% versus 87.3% (P=0.04). In multivariable Cox analyses, impaired patient survival was significantly associated with elevated TCC (HR 1.40 (1.02-1.91), P=0.04) along with male sex, recipient and donor age, smoking, diabetes and overall more than one year in renal replacement therapy prior to engraftment. Likewise, elevated TCC was independently associated with graft loss (HR 1.40 (1.06-1.85), P=0.02) along with the same covariates. Finally, elevated TCC was in addition independently associated with death censored graft loss (HR 1.69 (1.06-2.71), P=0.03) as were also HLA-DR mismatches and higher immunological risk. Conclusions: Early complement activation, assessed by plasma TCC, was associated with impaired long-term patient and graft survival.